(untitled) (Wallingford, Oxon, UK, 1995)
The case for conserving biodiversity is well established on economic as well as scientific grounds. Biodiversity is essential for sustainable development, adaptation to a changing environment and the continued functioning of the biosphere - indeed, to human survival itself. Plant breeders are dependent upon the availability of a large pool of diverse genetic material represented by local races and wild relatives, since in themselves modern crop varieties provide too restricted a genepool for further breeding. Without the ability to draw from a diverse genetic reservoir, further improvement may not be possible. It is therefore essential that guidance is available on collecting plant germplasm.
Keywords: Plant breeding,Crops,Nhân giống cây trồng